Effectiveness of Antipyretic with Tepid Sponging Versus Antipyretic Alone in Febrile Children: A Randomized Controlled Trial - Basavaraj, Chetak Kadbasal; Pocha, Shyamala Gowri; Dhati, Ravi Mandyam (Journal of Nepal Paediatric Society, 2018)
Introduction: Fever is the most common presenting complain for which children are brought to the paediatrician.Physical methods are widely used in treating febrile children, tepid sponging being commonly practiced in hospitals along with antipyretics. The objectives of this study were to compare the effectiveness of tepid sponging and antipyretic drug versus antipyretic drug alone in febrile children. Material and Methods: This was a Randomized controlled trial done in JSS Medical College and Hospital. All children under the age of 6 months to 12 years, admitted with axillary temperature of >99oF were included in the study. A total of 500 children were included over two years study period. Children with recorded axillary temperature of >990F were randomized into control and study group by computer generated randomisation. Children in the control group received only paracetamol (15mg/kg) at 5 minutes and combined group received paracetamol and tepid sponging at five minutes. Axillary temperature was monitored every 15 minutes for a period of 2 hours in both the groups. Results: There is no significant difference in reduction of temperature between the two groups by the end of two hours. Children in combined group had a higher level of discomfort than those in only antipyretic group. Conclusion: Tepid sponging does not add to the efficacy of paracetamol in antipyresis and that addition of tepid sponging to antipyretic, results in additional discomfort for the child. This study, therefore, endorses the view that antipyretic alone without tepid sponging should be the modality of therapy in children with fever.